INCOME AND BUSINESS FEASIBILITY ANALYSIS OF TOFU AND TEMPEH AGROINDUSTRY - Baru, Babtisa Resa; Abdurrahman, Mustafa; Illu, Abraham R. (Undana Press, 2025)
The study aims to analyze the income and financial feasibility of tofu agroindustry business in CV Sumber Hidup Mata Air Village, Central Kupang Regency. The sampling technique used a non-probability sampling technique, namely by using a case study technique. The data used in this study are primary and secondary data. To determine the feasibility of the tofu agroindustry business and at CV Sumber Hidup, feasibility analysis was carried out using the R/C ratio, Break Event Point (BEP), Net Present Value (NPV), Internal Rate Of Return (IRR), Net B/C Ratio, Return On Investment (ROI), and Payback Period (PP). The results of this study indicate that the income of the tofu business at CV Sumber Hidup is IDR 693,837,025/ year and the CV Sumber Hidup tofu business is declared feasible with an R/C ratio value of 1.30> 1, Net Present Value (NPV) of IDR. 941,780. 947.98, - with NPV>0 criteria, Internal Rate Of Return (IRR) of 45% with IRR>DR (9%) criteria, Net B / C ratio of 1.30>1, Return On Investment (ROI) of 112% high investment return rate while Payback Period (PP) 1 year 3 months.